Youth's literary socialisation practices online: A systematic review of research. (June 2022) - Santa María, Luz; Aliagas, Cristina; Rutten, Kris
Abstract: This systematic research review arises from the need to conceptualise youth's literary socialisation practices in the current digital landscape to advance knowledge in literary education. The broad uses of socialisation in this research area prompted us to define this concept carefully to situate our research questions. Through a seven-step methodological approach that included database search and grounded theory thematic analysis, we asked the research available in Web of Science and Scopus databases: What are the literary socialisation practices in which adolescents engage online as studied by research? The analysis of thirty publications led to elaborating three themes to explain youth's literary socialisation practices online, namely, travelling practices, fluid identities and roles, and collaborative transmedia literacies. These findings are further discussed in the final section to propose that the digital is an enabling environment for youngsters to build meanings and feelings on the literature they read and write, through performing varied identities and roles, engaging in connected learning, and recognising affect as a valid form of experiencing fiction. We finalise with implications for literary education and the theoretical contributions of the geographies of youth for future research in this field.